The Difference of Implementation Between Reflexology Massage and Combination of Exercises With Reflexology Massage for Elderly With Insomnia - Hafna Rosyita; Dewi Atika Putri; Anindini Winda; Dwi Ratna Sari Handayani; Muhammad Arsyad Subu; RM Alfian (Syntax Corporation Indonesia, 2024)
Introduction: The older people have various health problem and one of them is insomnia. Physiologic changes of aging, environmental conditions, and chronic medical illnesses contribute to insomnia among elderly. Insomnia in this population is associated with decreased memory, impaired concentration, and impaired functional performance. Objective: The objective of this study was to investigate the condition of insomnia among elderly after being given combined exercise with reflexology and reflexology only before and after the intervention. Method: This research used a quasi-experimental design with pre-post design with the control group. Sampling was carried out systematically during the study period with samples was taken according to inclusion criteria. The target number of samples is set using the difference formula average. The instruments that measure Imsonia used is PIRS. Data analysis was carried out on all subjects in both groups A and B with analysis statistics measuring the difference between PIRS before and after intervention. Results: The results of the Mann-Whitney test before the intervention in group A obtained a mean rank of 16.07. Before the intervention in group B obtained a mean rank of 19.45. Statistically, it showed that the difference was not significant, p=0.33 (p>0.05). The results of the Mann-Whitney test after intervention in group A had a mean rank of 22.10 and after intervention in group B had a mean rank of 14. 93. Statistically showed a significant difference, p=0.04 (p<<0.0) Conclusion: We found that there was a change in the condition of insomnia before and after the combination intervention (group A). The average decrease in insomnia scores for the elderly was carried out using the Pittsburg Insomnia Rating Scale (PIRS) questionnaire> However, there was no change in the condition of insomnia. statistically significant. Likewise, in group B, the average insomnia score decreased and was statistically significant